Metabolic engineering of an acid-tolerant yeast strain Pichia kudriavzevii for itaconic acid production - Sun, Wan; Vila-Santa, Ana; Liu, Na; Prozorov, Tanya; Xie, Dongming; Faria, Nuno Torres; Ferreira, Frederico Castelo; Mira, Nuno Pereira; Shao, Zengyi (Metabolic engineering communications, 2020)
Itaconic acid (IA), or 2-methylenesuccinic acid, has a broad spectrum of applications in the biopolymer industry owing to the presence of one vinyl bond and two acid groups in the structure. Its polymerization can follow a similar mechanism as acrylic acid but additional functionality can be incorporated into the extra beta acid group. Currently, the bio-based production of IA in industry relies on the fermentation of the filamentous fungus Aspergillus terreus. However, the difficulties associated with the fermentation undertaken by filamentous fungi together with the pathogenic potential of A. terreus pose a serious challenge for industrial-scale production. In recent years, there has been increasing interest in developing alternative production hosts for fermentation processes that are more homogenous in the production of organic acids. Pichia kudriavzevii is a non-conventional yeast with high acid tolerance to organic acids at low pH, which is a highly desirable trait by easing downstream processing. We introduced cis-aconitic acid decarboxylase gene (cad) from A. terreus (designated At_cad) into this yeast and established the initial titer of IA at 135 ​± ​5 ​mg/L. Subsequent overexpression of a native mitochondrial tricarboxylate transporter (herein designated Pk_mttA) presumably delivered cis-aconitate efficiently to the cytosol and doubled the IA production. By introducing the newly invented CRISPR-Cas9 system into P. kudriavzevii, we successfully knocked out both copies of the gene encoding isocitrate dehydrogenase (ICD), aiming to increase the availability of cis-aconitate. The resulting P. kudriavzevii strain, devoid of ICD and overexpressing Pk_mttA and At_cad on its genome produced IA at 505 ​± ​17.7 ​mg/L in shake flasks, and 1232 ​± ​64 ​mg/L in fed-batch fermentation. Because the usage of an acid-tolerant species does not require pH adjustment during fermentation, this work demonstrates the great potential of engineering P. kudriavzevii as an industrial chassis for the production of organic acid. •Pichia kudriavzevii is a non-conventional yeast with high acid tolerance to organic acids at low pH.•Engineering P. kudriavzevii to produce itaconic acid, a highly sought after biopolymer precursor.•First description of a cis-aconitic acid transporter identified from a host besides the native producer of itaconic acid.•Discussion on the potential of P. kudriavzevii as an industrial chassis for the production of organic acids.